Immunological profile of peripheral blood lymphocytes and monocytes/macrophages in Kawasaki disease - Matsubara, T (Blackwell Science Inc, 2005)
Kawasaki disease (KD) is an acute illness of early childhood characterized by prolonged fever, diffuse mucosal inflammation, indurative oedema of the hands and feet, a polymorphous skin rash and nonsuppurative lymphadenopathy. The histopathological findings in KD comprise panvasculitis with endothelial necrosis, and the infiltration of mononuclear cells into small and medium-sized blood vessels. The levels of many proinflammatory cytokines, chemokines and adhesion molecules can be elevated in sera from children with KD at the acute stage. Although many immunological studies on KD involving peripheral blood have been reported, the data obtained remain controversial. This review focuses on the immune response of peripheral blood lymphocytes and monocytes/macrophages during acute KD.